Low soil available phosphorus level reduces cotton fiber length via osmoregulation - Sun, Miao; Zheng, Cangsong; Feng, Weina; Shao, Jingjing; Pang, Chaoyou; Li, Pengcheng; Dong, Helin (Frontiers in Plant Science, 2023)
Introduction Phosphorus (P) deficiency hinders cotton (Gossypium hirustum L.) growth and development, seriously affecting lint yield and fiber quality. However, it is still unclear how P fertilizer affects fiber length. Methods Therefore, a two-year (2019-2020) pool-culture experiment was conducted using the split-plot design, with two cotton cultivars (CCRI-79; low-P tolerant and SCRC-28; low-P sensitive) as the main plot. Three soil available phosphorus (AP) contents (P0: 3 ± 0.5, P1: 6 ± 0.5, and P2 (control) with 15 ± 0.5 mg kg−1) were applied to the plots, as the subplot, to investigate the impact of soil AP content on cotton fiber elongation and length. Results Low soil AP (P0 and P1) decreased the contents of the osmotically active solutes in the cotton fibers, including potassium ions (K+), malate, soluble sugar, and sucrose, by 2.2–10.2%, 14.4–47.3%, 8.7–24.5%, and 10.1–23.4%, respectively, inhibiting the vacuoles from facilitating fiber elongation through osmoregulation. Moreover, soil AP deficiency also reduced the activities of enzymes participated in fiber elongation (plasma membrane H+-ATPase (PM-H+-ATPase), vacuole membrane H+-ATPase (V-H+-ATPase), vacuole membrane H+-translocating inorganic pyrophosphatase (V-H+-PPase), and phosphoenolpyruvate carboxylase (PEPC)). The PM-H+-ATPase, V-H+-ATPase, V-H+-PPase, and PEPC were reduced by 8.4–33.0%, 7.0–33.8%, 14.1–38.4%, and 16.9–40.2%, respectively, inhibiting the transmembrane transport of the osmotically active solutes and acidified conditions for fiber cell wall, thus limiting the fiber elongation. Similarly, soil AP deficiency reduced the fiber length by 0.6–3.0 mm, mainly due to the 3.8–16.3% reduction of the maximum velocity of fiber elongation (VLmax). Additionally, the upper fruiting branch positions (FB10–11) had higher VLmax and longer fiber lengths under low soil AP. Discussion Cotton fibers with higher malate content and V-H+-ATPase and V-H+-PPase activities yielded longer fibers. And the malate and soluble sugar contents and V-H+-ATPase and PEPC activities in the SCRC-28's fiber were more sensitive to soil AP deficiency in contrast to those of CCRI-79, possibly explaining the SCRC-28 fiber length sensitivity to low soil AP.